Occurrence of Two Pentatomid Bugs, Halys dentatus Fabr. and Erthesina fullo Thunb., Together on some Economic Forest Trees and their Seasonal Occurrence - Dhiman, S. C.; Yadav, Y. K.; Sharma, Deepti (Indian Forester, 2004)
No abstract